Age and Geochemical Characteristics of Nansu Rapakivi Granite in Jiaobei Uplift Belt, Qingdao - Qiao, Feng; Rongtian, Sheng; Xuewei, Li; Ruiwen , Dai; Yong, Jiang (Global Journal of Earth Science and Engineering, 2022)
LA-ICP-MS zircon U-Pb geochronology from Nansu large Rapakivi granite in the Jiaobei uplift belt shows the concordant age is 116.5±0.32Ma and the weighted average age is 116.7±0.89Ma, belonging to the late Yanshanian products of Early Cretaceous. The rock geochemical characteristics show that the SiO2 content of rapakivi granite ranges from 70.30% to 71.65%, with an average of 70.975%, A / CNK is 0.871 ~ 0.895 (average 0.883). K2O content is 4.70 ~ 5.75%, with an average of 5.14%, which is characterized by high potassium. Regarding trace elemental patterns, all the studied samples are enriched in large一ion-lithophile elements, e.g., K and Rb, and depleted in high-field-strength elements, e.g., Nb, Ta, and Ti. In terms of the chondrite-normalized rare earth element patterns, the Nansu samples are characterized by the strong enrichment of light rare earth elements (LREE) compared with heavy rare earth elements (HREE) and the absence of negative Eu anomalies. The Nansu ring porphyry granite is of high Sr and low Yb type, belonging to type I adakite, and formed in a high-pressure medium high-temperature environment of about 23km at depth and about 670oC. It is speculated that it was formed in the island arc environment and is related to the subduction of the Mesozoic Pacific plate.